If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6y = 8y + -10 Reorder the terms: 6 + 6y = -10 + 8y Solving 6 + 6y = -10 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 6 + 6y + -8y = -10 + 8y + -8y Combine like terms: 6y + -8y = -2y 6 + -2y = -10 + 8y + -8y Combine like terms: 8y + -8y = 0 6 + -2y = -10 + 0 6 + -2y = -10 Add '-6' to each side of the equation. 6 + -6 + -2y = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -2y = -10 + -6 -2y = -10 + -6 Combine like terms: -10 + -6 = -16 -2y = -16 Divide each side by '-2'. y = 8 Simplifying y = 8
| 10x^2+9x-6=0 | | 5+2x=7-r | | 6x-5x+2=6+5x-4(1+4x) | | 4(a+3)=18-2(32-2a) | | log(I)=1.5 | | 100+2x=-500 | | 5w+21=8w-30 | | 100+2x=500 | | Y=4x^3-0.5x+2 | | 17.70=p+p(0.03)(6) | | F(x)=x^2-20 | | 0=4x^3-0.5x+2 | | 8v^2-8v-13=0 | | 0.80+x=252 | | F(x)=4x^3-0.5x+2 | | u-20=6u-120 | | 100-2x=500 | | (x-9)2=(x-3)2 | | 81=3w*9 | | s+2=3s-5 | | 9m+6n-2m+8n= | | 2m^2+6m-20=0 | | -14-x=-2x+10 | | 10x+6=10x-6 | | -x-85=-12x+179 | | 7y-12=4y-3 | | 9x+3x-10=4(3x+1) | | -3x-64=-11x+120 | | 4w-9=3w+2 | | 3x+5(3)= | | -64y=-8 | | 4y-3x=9 |